Russian olive (Elaeagnus angustifolia L.): From a variety of traditional medicinal applications to its novel roles as active antioxidant, anti-inflammatory, anti-mutagenic and analgesic agent - Rafie Hamidpour (Journal of Traditional and Complementary Medicine, 2017)
Elaeagnus angustifolia L., which is commonly known as oleaster or Russian olive, is a deciduous plant from Elaeagnacea family. This plant can tolerate and survive a wide variety of environmental conditions. Different parts of E. angustifolia plant, especially the fruits and flowers, have been used traditionally in treating a variety of common illnesses such as nausea, cough, asthma, fever, jaundice, and diarrhea. The use of fruit powder and extract of E. angustifolia L. have shown to be effective in alleviating pain in patients with rheumatoid arthritis and also in reducing the healing time of wounds in injured person. In addition, some recent reports have indicated the anti-oxidant, anti-inflammatory, antimicrobial, anticancer and some other properties of oleaster plant. The other important property of this plant would be its role in bio-monitoring the environment for some toxic elements and also its action as a bio-fertilizer agent in distressed lands. It seems that with more advanced studies on E. angustifolia L. and its bioactive components, this plant might be potentially effective and can be used as a natural alternative resource in pharmaceutical industries for treating chronic and serious problems, Fig. 1.